ANALISIS KANDUNGAN BIOAKTIF SARANG SEMUT (Myrmecodia pendens) ASAL KAMPUNG YENBESER SEBAGAI ANTIOKSIDAN - Yemima Dimara (JURNAL ETNOFARMASI, 2025)
Free radicals are reactive molecules that can cause cell damage through oxidative processes and are major factors in various degenerative diseases such as cancer, diabetes, and heart disease. The neutralization of free radicals can be achieved by antioxidant compounds that inhibit oxidation reactions. One plant with potential as a natural antioxidant source is the ant plant (Myrmecodia pendens), traditionally used by the Raja Ampat community to treat various diseases. This study aimed to identify bioactive compounds and evaluate the antioxidant activity of the ethanol extract of the ant plant originating from Yenbeser Village, Raja Ampat Regency. This research was an experimental laboratory study using the maceration method with 70% ethanol as a solvent. Antioxidant activity was measured using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method with a UV-Vis spectrophotometer at a wavelength of 517 nm using vitamin C as a positive control. The results showed an extract yield of 17.15%, with bioactive compounds identified as flavonoids, tannins, and alkaloids, while saponins were not detected. The IC₅₀ value obtained was 150,62 µg/mL, categorized as strong antioxidant activity. In conclusion, the ethanol extract of the ant plant (Myrmecodia pendens) from Yenbeser Village has strong antioxidant activity and potential to be developed as a natural antioxidant source for phytopharmaceuticals and traditional medicines based on West Papua natural resources